Determinant of Digital Leadership on Business Success and Sustainability Performance: A Systematic Literature Review - Theryo, Kevin; Setiawan, Yansen Yasanando; Ongko, Ricky; Edward, Edward; Fawwaz, Muhammad (Prodi Akuntansi UIN Sunan Ampel Surabaya, 2026)
Purpose: This study addresses a critical research gap, while rapid technological development reshapes organizational competitiveness, evidence on how digital leadership specifically drives long-term sustainable performance remains highly fragmented. Consequently, this study aims to systematically examine the role of digital leadership in achieving business success and sustainability in the digital transformation era. Methodology/approach: Using the PRISMA and SALSA approach, twenty peer-reviewed articles (2015–2025) were screened, evaluated, and analyzed thematically. Findings: Findings reveal that digital leadership positively influences business success and sustainability, with digital capability, culture, affective commitment, and top-management innovativeness serving as key mediators. Practical implications: The study concludes that strengthening digital leadership is essential for firms to achieve competitive advantage and sustainability outcomes, offering strategic implications for policy, organizational development, and future academic research. Originality/value: This research addresses a fundamental gap in prior studies, the absence of an integrated framework for digital leadership. The novelty lies in synthesizing ten years of systematic literature to comprehensively map the determinants, mediators, and outcomes of digital leadership on business and sustainability performance.